2015
DOI: 10.22317/jcms.v1i1.88
|View full text |Cite
|
Sign up to set email alerts
|

VitaminD deficiency and hypertension in type 2 diabetic Iraqi patients

Abstract: Objective Vitamin D3 deficiency has been defined as serum 25-hydroxyvitamin D3[25-(OH)D3] levels below 30 ng/ml and it is common among patients with type 2 diabetes mellitus (T2DM). Laboratory studies indicate that 1,25-(OH)D3 suppresses renin expression and vascular smooth muscle cells proliferation, then decreases blood pressure. The aim of the present study is to demonstrate the association between 25-(OH)D3 level and the risk of blood pressure, and its relation with T2DM and body mass index (BMI).Method Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…This was agreed with the results of this study which revealed that serum Osteocalcin level in T2DM patients was significantly higher than in control. In this study, there was a significant decrease in serum HDL-C in T2DM patients when compared with non-diabetic healthy control and this is in accordance with the study of Al-Tu'ma et al [51]. Because androgen and estrogen receptors are present in visceral and subcutaneous adipocytes, endogenous sex hormones have altered the lipid profile in postmenopausal women.…”
Section: Resultssupporting
confidence: 92%
“…This was agreed with the results of this study which revealed that serum Osteocalcin level in T2DM patients was significantly higher than in control. In this study, there was a significant decrease in serum HDL-C in T2DM patients when compared with non-diabetic healthy control and this is in accordance with the study of Al-Tu'ma et al [51]. Because androgen and estrogen receptors are present in visceral and subcutaneous adipocytes, endogenous sex hormones have altered the lipid profile in postmenopausal women.…”
Section: Resultssupporting
confidence: 92%